Potential of Coconut Fiber-Based Liquid Smoke as Biofungicide to Suppress Phytophthora palmivora Fungus Growth In Vitro - Asrul, Asrul; Rosmini, Rosmini; Egayani, Egayani; Mutmainah, Mutmainah; Jusriadi, Jusriadi (Universitas Gadjah Mada, 2023)
The presence of pod rot caused by the pathogenic fungus Phytophthora palmivora (Butl.) is a major constraint in cocoa cultivation. Control of this disease needs to be done with an organic approach that is environmental friendly such as the use of biopesticides from plant materials. Coconut fiber liquid smoke is one of the materials that can be used as an environmental friendly botanical pesticide. This study aims to determine the concentration of liquid smoke made from coconut fiber that is effective in inhibiting the growth of the pathogenic fungus P. palmivora in vitro. The experiment was arranged in a non-factorial Randomized Complete Block Design (CRD) consisting of six treatments and five replicates, for a total of 30 experimental units. The experiment was conducted using the food poisoned technique, which is mixing 10 ml PDA media with liquid smoke (2 ml of each concentration). The liquid smoke treatment consisted of 0% (control), 2%, 4%, 6%, 8% and 10% concentrations. The results of the in vitro test showed that the application of coconut fiber liquid smoke with a concentration of 10% on PDA media can suppress the growth and inhibit the development of P. palmivora (Butl.) fungal colonies until they do not grow (0 cm).